2009
DOI: 10.1016/j.ajhg.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Metalloprotease ADAM9 Leads to Cone-Rod Dystrophy in Humans and Retinal Degeneration in Mice

Abstract: Cone-rod dystrophy (CRD) is an inherited progressive retinal dystrophy affecting the function of cone and rod photoreceptors. By autozygosity mapping, we identified null mutations in the ADAM metallopeptidase domain 9 (ADAM9) gene in four consanguineous families with recessively inherited early-onset CRD. We also found reduced photoreceptor responses in Adam9 knockout mice, previously reported to be asymptomatic. In 12-month-old knockout mice, photoreceptors appear normal, but the apical processes of the retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 38 publications
1
53
1
Order By: Relevance
“…Danciger et al described a ‘small’ posterior subcapsular cataract in the large Brazilian family 11. This observation was not described in a more recent article which included three other families with ADAM9 arCRD 6. In our study, the mother presented with an anterior polar and a posterior subcapsular cataract, but the two children affected by CRD did not, whereas three children out of the four unaffected by CRD showed dot cataract.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Danciger et al described a ‘small’ posterior subcapsular cataract in the large Brazilian family 11. This observation was not described in a more recent article which included three other families with ADAM9 arCRD 6. In our study, the mother presented with an anterior polar and a posterior subcapsular cataract, but the two children affected by CRD did not, whereas three children out of the four unaffected by CRD showed dot cataract.…”
Section: Discussioncontrasting
confidence: 79%
“…Although mutations in ABCA4 are found in 24–65% of arCRD,1 3 8–10 many patients remain without molecular diagnosis. In 2009, Parry et al 6 observed that mutations in the ADAM metallopeptidase domain 9 ( ADAM9 ) gene were responsible for the arCRD observed in a Brazilian family first described and mapped under CORD9 by Danciger et al in 2001 11…”
Section: Introductionmentioning
confidence: 99%
“…Three of these genes initially have been associated with ACHM, a form of cone dysfunction that can develop into COD. Eighteen genes have been associated with ar CRD (ABCA4, 17 ADAM9, 18 C8orf37, 19 CDHR1, 20,21 CERKL, 22 CNGB3, 23 CRB1, 24 CRX, 24 EYS, 25 FSCN2, 26 GUCY2D, 27 KCNV2, 14 PDE6C, 23 POC1B, 28,29 PROM1, 30 RAB28, 31 RPE65, 24 RPGRIP1, 23 and TULP1 16 ). In both disorders, mutations in these genes explain disease in an estimated 21% (COD) and 25% (CRD) of patients.…”
mentioning
confidence: 99%
“…The regions encompass a total of 190 refseq genes. 11 Of the six arCRD causative genes known to date (ABCA4, 12 ADAM9, 13 C8orf37, 1 CERKL, 14 RPGRIP1, 15 and CDHR1 16 ), C8orf37 was the only one included in a homozygous interval. Since the phenotype in both affected siblings was consistent with the diagnosis of CRD, C8orf37 appeared to be the best candidate gene in this family.…”
Section: Genetic Analysesmentioning
confidence: 99%